Decolonization of brazilian theater: periphery epistemologies - Conceição, Raylson Silva (Farol, 2024)
This study addresses the disparity in documentation and visibility of theatrical productions in the North and Northeast regions of Brazil compared to the Southeast in contemporary times. The analysis is grounded in decolonial approaches and the geopolitics of knowledge, aiming to unveil the reasons behind this discrepancy. The research emphasizes the importance of including diverse forms of theatrical expression to create a representative narrative of Brazilian theater. It is concluded that the decolonization of knowledge is essential for a more inclusive and authentic approach in the field of Brazilian theatrical studies.
Keywords: Brazilian theater; decolonization; North and Northeast regions; representative narrative